Alternative Use Systems for the Remaining Cloud Forest in Ethiopia and the Role of Arabica Coffee - A Cost-Benefit Analysis - Anke Reichhuber; Till Requate (Kiel University, Department of Economics, 2007)
This paper presents a cost-benefit analysis of three different use systems for the remaining cloud forests in Ethiopia which at present are being depleted at a rate of 8% per year. These use systems are traditional conversion to crop land, sustainable management of the forest (e.g. by growing high-quality semi-forest coffee), and strict protection. We find that conversion to cropland yields the highest net present income value for the local population, and at discount rates of 10% is even in the best interests of the country. For discount rates of at 5% or lower, sustainable forest use is in the best interests of the country. Taking into account the global benefits of biodiversity conservation and carbon storage, sustainable forest management yields the highest total economic value.
Keywords: 330; cost-benefit analysis; biodiversity; coffee; Ethiopia